A low-cost apparatus for transforming Drosophila and detecting green fluorescent protein (GFP) genetic markers - Maríndia Deprá; Lenira Maria Nunes Sepel; Élgion Lucio da Silva Loreto (Genetics and Molecular Biology, 2004)
We describe the transformation of white mutant Drosophila simulans with a piggyBac transposon vector and a green fluorescent marker (GFP) and show how to construct inexpensive micro-manipulation and epifluorescence equipment for use in transposon-mediated germ-line transformation. Although the number of G0 adult flies (16) obtained in relation to the number of injected eggs was very low (12.5%) it was comparable to the proportion described by other authors and can be considered as a good rate of transformation.